Consumer Perspectives On Csr Representations In Unilever Advertising: A Phenomenological Study - Andi Renita Puspayanti; Brigita MB; Annisa Muthmainnah Ichwan; Darwis; Arifuddin (Journal of Creative Power and Ambition (JCPA), 2026)
This study aims to understand consumer perspectives on the representation of Corporate Social Responsibility (CSR) in Unilever advertisements. The study employed a qualitative phenomenological approach through in-depth interviews with ten informants who had watched Unilever CSR advertisements and used its products. Data were analyzed using Interpretative Phenomenological Analysis (IPA). The findings show that CSR representation in advertisements is perceived as an effort to build a positive corporate image and gain public trust. CSR advertisements also create emotional closeness with consumers by addressing social issues related to everyday life. However, some consumers remain skeptical and perceive CSR messages as more image-building than genuine social concern. Nevertheless, consumers still view CSR as an important social responsibility that companies should carry out. This study indicates that CSR representation in advertising influences consumers’ perceptions, experiences, and trust toward the company. Therefore, the effectiveness of CSR communication depends on the consistency between social messages in advertisements and the company’s actual practices.